COVID-19 Pathophysiology: Inflammation to Cardiac Injury - Sami Fouda; Robert Hammond; Peter D Donnelly; Anthony R M Coates; Alexander Liu (Hearts)
Coronavirus disease 19 (COVID-19) is responsible for one of the worst pandemics in human history. The causative virus, the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), can invade host cells in multiple organs by binding the angiotensin-converting enzyme (ACE) II expressed on the cell surface. Once inside the host cell, viral replication takes place, leading to cellular disruption and the release of signal molecules that are recognised by the innate immune system. Innate immunity activation leads to the release of proinflammatory cytokines and primes the adaptive immune system. The proinflammatory environment defends against further viral entry and replication. SARS-CoV-2 infection is thought to lead to myocardial injury through several mechanisms. Firstly, direct viral-mediated cellular invasion of cardiomyocytes has been shown in in vitro and histological studies, which is related to cellular injury. Secondly, the proinflammatory state during COVID-19 can lead to myocardial injury and the release of protein remnants of the cardiac contractile machinery. Thirdly, the hypercoagulable state of COVID-19 is associated with thromboembolism of coronary arteries and/or other vascular systems. COVID-19 patients can also develop heart failure; however, the underlying mechanism is much less well-characterised than for myocardial injury. Several questions remain regarding COVID-19-related heart failure, including its potential reversibility, the role of anti-viral medications in its prevention, and the mechanisms underlying heart failure pathogenesis in long COVID-19. Further work is required to improve our understanding of the mechanism of cardiac sequelae in COVID-19, which may enable us to target SARS-CoV-2 and protect patients against longer-lasting cardiovascular complications.